Relationship Between Prosthodontic Treatment and Nutritional Status: A Review - Basnet, Bishal Babu; Limbu, Indra Kumar; Alhajj, Mohammed Nasser; Rokaya, Dinesh (Birat Journal of Health Sciences, 2018)
Pertinent literature search about changes or eﬀects of prosthodontic treatment on nutritional status was performed. The articles were electronically and hand searched in all available journals including research works, reviews, randomized controlled trials and systematic reviews. The information were obtained to answer the question whether denture therapy has a role in altering nutritional intake or not. Most articles agreed that the risk of malnutrition is elevated by being edentulous. However, there were contrasting results about improvement of nutrition by providing prosthodontic treatment. Thus, many authors have emphasized the role of nutritional counseling along with denture therapy for the beneﬁts of geriatric patients who undergo the inevitable process of being edentulous. BJHS 2018;3(1)5 : 385 - 389